The Best American Newspaper Narratives, Volume 6 - Reaves, Gayle, 1958- (Mayborn best American newspaper narrative series, 2019)
This anthology collects the eleven winners of the 2018 Best American Newspaper Narrative Writing Contest at the Mayborn Literary Nonfiction Conference, an event hosted by the Frank W. Mayborn Graduate Institute of Journalism at the University of North Texas.